2013
DOI: 10.3834/uij.1944-5784.2013.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Change in Renal Function in Patients Undergoing Continent vs Noncontinent Urinary Diversions

Abstract: Introduction: Despite good supporting evidence, the dogma still exists that patients with renal insufficiency are not good candidates for continent diversions. In this paper, we attempt to evaluate this relationship and investigate the short-term effects of continent and noncontinent diversions on patients with both normal renal function and preexisting renal insufficiency. Methods: From Sept 2004 to June 2009, 212 adult patients underwent radical cystectomy and intestinal urinary diversion by a single surgeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Jin et al [7] followed a group of 161 patients (50 IC, 111 ONB) for a median of 10 years. In 204 [4]. Despite the short follow-up period of 18 months, we showed that there was no significant difference in decline in GFR between patients receiving IC vs continent diversion (P = 0.49).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Jin et al [7] followed a group of 161 patients (50 IC, 111 ONB) for a median of 10 years. In 204 [4]. Despite the short follow-up period of 18 months, we showed that there was no significant difference in decline in GFR between patients receiving IC vs continent diversion (P = 0.49).…”
Section: Discussionmentioning
confidence: 70%
“…In this group, 36% of patients with IC and 21% of patients with ONB showed a decline in GFR of >10 mL/min/1.73 m 2 at 10 years after surgery, with 38% of patients with IC and 22% of patients with ONB developing CKD Stage III–V [7]. Our group has previously attempted to address the difference in GFR decline among different types of diversion in a relatively small cohort of 168 patients (44 IC, 109 ONB, 15 CCUD) with preexisting renal insufficiency (GFR 40–59 mL/min/1.73 m 2 ) [4]. Despite the short follow‐up period of 18 months, we showed that there was no significant difference in decline in GFR between patients receiving IC vs continent diversion ( P = 0.49).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations